The relationship between the levels of supervisor support and transfer of training :a case study in one selected company in Kuching - Hazlawati, Ali Baba (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study aims to explore the trainee's perception on the levels of supervisor support and transfer of training. This study of relationship was conducted in one selected company in Kuching, Sarawak. The study incorporates a sample of 86 respondents by using the method of simple random sampling. Their responses were collected by using the apparatus of questionnaire and were analyzed using One-Way Analysis of Variance (ANOVA) and Pearson Correlation. The ANOVA was used to test the differences between the demographic factors of respondents such as age, academic background and length of service. The Pearson Correlation on the other hand, was used to understand the relationship between the selected independent variables of the research (supervisor support in terms of acceptance, encouragement, participation, reinforcement practice skills and teaching in program) with the dependent variable (transfer of training). The statistical analysis showed that, only one demographic factor (length of service) had an impact to transfer of training. All independent variable have positive relationship with transfer of training except for supervisor support in terms participation. Thus, supervisor supports were crucial for transfer of training in the workplace. Therefore, both human resource development (HRD) practitioners and management of the organization should work together to maximize transfer of training. Transfer of training should be facilitated by providing supervisors support to trainees in order to ensure positive transfer.